Antibodies against cell membrane constituents in systemic lupus erythematosus and related diseases. I. Cytoxic effect of serum from patients with systemic lupus erythematosus (SLE) for allogenic and for autologous lymphocytes - Stastny, P. (1971)
When single random serums from sixty patients with systemic lupus erythematosus (SLE) were examined for cytotoxicity against allogeneic lymphocytes, thirty-six or 60% were found to be cytotoxic. In controls, consisting of eighteen blood bank donors, forty-five clinic patients matched to the SLE group, and 366 multiparous women, cytotoxicity was found in 0, 4 and 12% respectively. When 151 serums from twenty SLE patients were tested against their own lymphocytes, twenty-four serums from twelve patients gave autologous reactions. Cytotoxicity of SLE serums for both allogeneic and autologous lymphocytes was complement dependent and could be specifically absorbed with reactive lymphocytes, suggesting that the factor responsible for cytotoxicity was an antibody. Since activity was present at 37°C, cytotoxicity may be assumed to be manifest in vivo. These antibodies may play a role in the leukopenia of SLE and may also be responsible for other manifestations of multisystem disease.